Profitabilitas, Leverage, Corporate Social Responsibility Dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan - Eny Maryanti; Ruci Arizanda Rahayu; Ika Putri Mujirahayu (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
: Basically, the main goal of a company is to achieve maximum profit by producing a product and/or service that is able to be competitive in the market so as to increase the value of the company. The main purpose of this research is to find out whether profitability, leverage, corporate social responsibility and company growth can affect the value of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The period taken in this study is from 2018 - 2020. The population specified in the study includes all companies in manufacturing for the period 2018 - 2020 on the Indonesia Stock Exchange. The research sample was taken using purposive sampling technique. The research population data are 261 companies and the samples obtained are 104 companies. The method for data analysis used is SPPS version 25. The results of the study state that profitability proxied by EPS (earnings per share) can have a significant positive effect on firm value, leverage proxied by DER (debt to equity ratio) can affect firm value but negative. Meanwhile, the corporate social responsibility disclosed by the company has a significant positive effect on the value of the company and the company's growth which is proxied by the company's sales (sales growth) also has a positive influence